The Instruments and Operating Procedures for Conducting Monetary Policy in the Group of Five Countries. (IMF Working Papers; Working Paper, 1989)
This paper examines and compares the instruments and procedures currently employed by the central banks of France, Germany, Japan, the United Kingdom, and the United States for implementing monetary policy in the short run. The analysis indicates that the monetary authorities of these five countries focus on influencing certain short-term interest rates in implementing monetary policy. Thus, to the extent that interest rate developments affect the behavior of exchange rates, this analysis facilitates ascertaining changes in monetary policies in the G-5 countries and their exchange rate implications.